Greetings in English and Vietnamese emails from a cross-cultural perspective / Cap Thi Phuong; Supervisor: Assoc.Prof.Dr. Ho Ngoc Trung - Cap, Thi Phuong
This study focuses on a cross - cultural comparison of greeting categories in English and Vietnamese emails in workplace and everyday life. This paper makes a significant contribution for future researchers, as it is of help to researchers in the speech act and cross- cultural area specifically in terms of English and Vietnamese emails. It will be also of help to those learning how to write emails in English and those who teach it in these two countries. Thus, the outcome of this research will contribute to depict the differences and the similarities in the use of greeting categories between two different groups of respondents from diverse linguistic and cultural domains. The greeting categories are analyzed with data taken from 100 English emails written by English native speakers and 100 emails written by Vietnamese people. Utilizing contrastive analysis, the author analyzed the greeting categories in English and Vietnamese emails. Results of the study showed that greeting in emails is a culturally significant even in universal terms. Especially in Vietnamese, greeting is an important part in culture life. Some issues considered as "a taboo" in English emails are used popularly in Vietnamese emails. There are specific cultural features in two languages. Then, some suggestions for the Vietnamese learners of English are presented based on the theory and the conductor's personal experience after studying.